Influence of SMAW Welding Current Variations on the Tensile Strength of API 5L Grade B Pipe - Weriono, Weriono; Rinaldi, Rinaldi; Rahmi, Rahmi; Mirfaturiqa, Mirfaturiqa (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2025)
Welding often fails or rejects weld joints on API 5L Gr.B material, which is a critical problem, because the pipe is a very important part. It will have fatal consequences for the production process. This research is proposed to study the effect of Shielded Metal Arc Welding (SMAW) process current variations on the tensile strength of API 5L Gr. B Pipe material. Results from previous investigations reveal that, single pass welded joint was found to possess adequate strength and meet requirements and the impact toughness for API 5L Gr.B steel pipe oil and gas. The parent material was superior to that of multi-pass weld zone and heat affected zone (HAZ) at all test of temperatures. The ultimate stress with 50 A welding is 295.31 MPa and the yield stress is 216.41 MPa. The tensile stress with a welding current of 140 A produces an ultimate strength of 261.98 MPa and a yield stress of 191.41 MPa so that the SMAW welding process by increasing the current can reduce the tensile strength of the welding results.